2010
DOI: 10.1097/brs.0b013e3181ee6bd4
|View full text |Cite
|
Sign up to set email alerts
|

Adult Spinal Deformity—Postoperative Standing Imbalance

Abstract: Good clinical outcome requires achieving proper spinopelvic alignment in the treatment of adult spinal deformity. Although variations in pelvic morphology exist, a framework has been established to determine ideal values for regional and global parameter in an individualized patient approach. When planning realignment surgery for adult spinal deformity, restoring low sagittal vertical axis and pelvic tilt values are critical goals, and should be combined with proportional lumbar lordosis to pelvic incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
349
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 958 publications
(364 citation statements)
references
References 18 publications
4
349
1
10
Order By: Relevance
“…Tao et al [29] have suggested that hybrid construct were not likely to prevent crankshaft phenomenon when compared to pedicle screws construct. This complication is essentially encountered with skeletally immature patients, and was not seen in our series as all patients showed a closed triradiate cartilage at the time of surgery.…”
Section: Hybrid Constructs and Kyphosis Correctionmentioning
confidence: 99%
“…Tao et al [29] have suggested that hybrid construct were not likely to prevent crankshaft phenomenon when compared to pedicle screws construct. This complication is essentially encountered with skeletally immature patients, and was not seen in our series as all patients showed a closed triradiate cartilage at the time of surgery.…”
Section: Hybrid Constructs and Kyphosis Correctionmentioning
confidence: 99%
“…For follow-up radiographs, the difference between a predicted high lumbar lordosis L1-S1, as by the equation LL = PI ? 9° [5], and the real lumbar lordosis was calculated Eur Spine J (2014) 23:180-191 183 The vertebra above the first disc revealing lordotic wedging is usually selected as the lowest instrumented vertebra (LIV). The selection of LIV also addresses the concerns of increased biomechanical stress at the thoracolumbar junction.…”
Section: Correctionmentioning
confidence: 99%
“…Moreover, it has also been proven that applying this method is directly related to improving the health and quality of the life of the patients with AIS (11,12). The patients who have significantly lost their lordosis often need to spend high energy and a compensatory and painful mechanism such as pelvic retroversion to maintain their gravity line and balance (13,14). The concept of spinopelvic compensatory mechanism was explained by some French researchers over 20 years ago, but it was published in the English-language papers for the first time in the past decade (15).…”
Section: Discussionmentioning
confidence: 99%